Distribution of Leishmania major zymodemes in relation to populations of Phlebotomus papatasi sand flies - Hamarsheh, Omar (BioMed Central, 2011)
Phlebotomus papatasi (Scopoli) (Diptera: Psychodidae) is the main vector of Leishmania major Yakimoff & Schokhor (Kinetoplastida: Trypanosomatidae), the causative agent of zoonotic cutaneous leishmaniasis in the Old World. Multilocus enzyme electrophoresis (MLEE) was extensively used to type different L. major stocks allover the world. Multilocus microsatellite typing (MLMT) has been recently used to investigate P. papatasi sand flies at population and subpopulation levels. In this article, the association between geographical distribution of L. major zymodemes and the distribution of populations and subpopulations of L. major vector; P. papatasi are discussed.